Pelatihan Digital Marketing bagi UMKM Upaya Meningkatkan Pemasaran dan Pencatatan Keuangan Sae Digital Akademi - Adinda, Amelia Putri (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2023)
This study aims to gain a general understanding of how MSME actors at Sae Digital Academy can utilize social media as a marketing tool such as Facebook, Twitter and Instagram more effectively. The purpose of this research is to answer the problems that may be faced by MSME business actors related to the current need for the use of digital technology. Financial records are very important, because the majority of MSME require accounting and technology knowledge, a deeper understanding of bookkeeping and the use of technology as a marketing tool is needed. Qualitative descriptive techniques and observations are used as data collection approaches. According to research findings, MSME players have not fully embraced social media marketing for their commercial purposes. The findings of this study are expected to help MSME actors improve marketing in the current digital era.